Improve Students’ Skills in Listening Comprehension by Using Song Based on Multimedia - Hariratul Jannah; Abdollah Abdollah; Syahria Majid (Fakultas Sastra - Universitas Muslim Indonesia, 2018)
In order to improve the quality of learning English, especially listening skills, students of the English Literature Study Program and the English Language Education Study Program submitted the research title